IMPLEMENTASI GREEN ECONOMY PT. INDOFOOD SUKSES MAKMUR TBK DI NIGERIA MELALUI DUFIL PRIMA FOODS PLC - Alexander Febri Tricahyo; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Abstract This research analyzed and describe the Implementation of Green economy by PT. Indofood Sukses Makmur Tbk in Nigeria through Dufil Prima Foods PLC, which is a business strategy that the company implements to implement environmentally friendly practices and aims to improve economic performance in Nigeria by increasing the welfare of the community, reducing environmental impact, and ensuring that the products produced meet high safety and quality standards. This research used a Pluralism perspective and the theory of sustainable development by Sutamihardja. The research method used is qualitative research method and data obtained through books, academic articles, official documents and internet archives. This research showed that the implementation of green economy by PT Indofood Sukses Makmur Tbk through Dufil Prima Foods PLC has already made some efforts to implement Green economy with several programs that prioritize taking into account the values of sustainable development and based on the 3 main pillars of sustainable development. Keyword: Green economy, Sustainable Development, PT. Indofood Sukses Makmur Tbk, Nigeria..